प्राकृत व्याकरण र ग्रिमको ध्वनि परिवर्तनको नियमको तुलना - Bhandari, Mahendra (Haimaprabha, 2026)
This study focuses on a comparative analysis of the phonetic transformations that occurred during the transition from Sanskrit to Prakrit, and the sound changes from Proto-Indo-European to Germanic languages (known as Grimm’s Law). Adopting a qualitative approach based on documentary analysis, this study primarily utilizes the comparative method to analyze the data. The main objective of this study is to examine how sounds were distributionally shifted based on their place of articulation during the linguistic transformation from Sanskrit to Prakrit, as well as from Proto-Indo-European to Germanic. In this study, the grammatical aphorisms (sutras) of Prakrit grammarians such as Vararuchi, Hemachandra, and Chanda are taken as primary evidence, against which the nature of Germanic sound change is compared based on Grimm’s Law. The findings reveal that during the phonetic transformation from Sanskrit to Prakrit, almost all sounds underwent a shift or redistribution based on their place of articulation. Along with these positional shifts, changes were also observed in their manner of articulation, voicing (phonation), and aspiration. When these sounds change, they do not disperse to distant places of articulation but rather shift to neighboring positions, or are pronounced from the same position while changing in terms of voicing and aspiration. In contrast, Grimm’s Law reveals a cyclical change in the quality or manner of articulation while the place of articulation remains constant. By comparing these two systems, this paper concludes that sound change from Sanskrit to Prakrit is primarily oriented toward distribution or decentralization, moving toward lenition (weakening/softening of sounds). Conversely, the changes in Grimm’s Law do not follow a distributed pattern based on the place of articulation, but are instead centered around fortition (strengthening) and a structural cyclical pattern.